Strength of fiber reinforced high-strength concrete with stirrups under direct shear - Saeed1, S. A.; Sarhat2, S. R. (Sulaimani Journal for Pure and Applied Sciences, 1999)
The paper presents an experimental investigation of the direct shear transfer behavior of fiber reinforced high-strength concrete. The experimental study was performed on steel fiber reinforced push-off specimens with or without conventional stirrups. For the specimens with plain steel fibers, significant increases in the shear strength of high-strength concrete were observed. In the tests involving the combination of steel fibers and conventional stirrups, major improvement in crack control and enhancement in shear strength were observed.